2018
DOI: 10.3847/1538-4357/aad17b
|View full text |Cite
|
Sign up to set email alerts
|

A Likely Supermassive Black Hole Revealed by Its Einstein Radius in Hubble Frontier Fields Images

Abstract: At cosmological distances, gravitational lensing can in principle provide direct mass measurements of supermassive black holes (SMBH). Here, we directly estimate the mass of a SMBH in the brightest cluster galaxy (BCG) of MACS J1149.5+2223 at z = 0.54 using one of the multiply-lensed images of a background spiral galaxy at z = 1.49 projected close to the BCG. A lensed arc is curved towards the BCG centre, corresponding to an intrinsically compact region in one of the spiral arms. This arc has a radius of curva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
(89 reference statements)
1
7
0
Order By: Relevance
“…However, they can reveal their presence through the gravitational distortion of (razor-thin) lensing arcs, which is the phenomenon we investigate in this paper. Interestingly, as this paper was close to completion, Chen et al (2018) reported a possible detection of an SMBH of mass 8.4 +4.3 −1.8 × 10 9 M offset by 4.4 ± 0.3 kpc from the centre of the main lensing galaxy, the brightest cluster galaxy of MACS J1149+2223.5 at z = 0.54. The presence of a SMBH is inferred through a kink-like distortion in one of the multiply-lensed images of the background source.…”
supporting
confidence: 65%
“…However, they can reveal their presence through the gravitational distortion of (razor-thin) lensing arcs, which is the phenomenon we investigate in this paper. Interestingly, as this paper was close to completion, Chen et al (2018) reported a possible detection of an SMBH of mass 8.4 +4.3 −1.8 × 10 9 M offset by 4.4 ± 0.3 kpc from the centre of the main lensing galaxy, the brightest cluster galaxy of MACS J1149+2223.5 at z = 0.54. The presence of a SMBH is inferred through a kink-like distortion in one of the multiply-lensed images of the background source.…”
supporting
confidence: 65%
“…Nevertheless, the detection of SMBHs in normal galaxies are still very difficult provided that vast majority of them are quiescent and faraway. Although some new approaches seem promising to detect SMBHs at cosmological distances, such as gravitational lensing (e.g., Mao et al 2001;Hezaveh et al 2015;Chen et al 2018) and future gravitational wave observations of SMBH mergers or the inspiral of compact stellar remnants consumed by SMBH, they are not so efficient and practical for the time being. Heaven will always leave a door open, the so-called tidal disruption event (TDE) could offer us the greatest chance to catch sight of these dormant SMBHs.…”
Section: Introductionmentioning
confidence: 99%
“…Given the clear cut prediction of the absence of the central image, various groups including Keeton (2003), Chen et al (2018), andInada et al (2008) have looked at optical and radio data of distant galaxies (z∼0.2-1) to search for the central image. Multiple studies have been focused on lensed radio galaxies as there is no contamination by the lens itself (e.g.…”
Section: Introductionmentioning
confidence: 99%